Utilização de algoritmo genético para reconfiguração de redes de distribuição de distribuição por meio da alocação de chaves - Lopes, Jessica Fernandes (2015)
The demand for electricity and the complexity of operations, has a large number of interconnections between protection systems. The power distribution thus becomes a major challenge in relation to the supply in order to make it sustainable and reliable. Behind the use of the available energy is a vast problem along with several factors, which directly influence the power supply, disruption and failures in the distribution system. The reconfiguration therefore is to change the topology of networks by opening or closing of the keys that interconnect the feeders, to optimize certain function. By minimizing asset losses, insulation faults, load balancing between the feeders improves the voltage levels. In this paper, we consider minimizing the total active loss through methodological development and implementation of Genetic Algorithm with Path Relinking in order to improve the searching to find the feasible solution. It is proposed, therefore, not via Mixed Integer Linear Programming (MILP), a new formulation for the Reconfiguration Problem in Distribution Systems.